High performance logic and circuits for high-speed electronic systems - Jain, F; Broadbridge, C; Gherasimova, M; Tang, H (World Scientific Publishing Co., 2019)
In this volume, we have put together papers spanning a broad range from the area of modeling of strain and misfit dislocation densities, microwave absorption characteristics of nanocomposites, to X-ray diffraction studies. Specific topics in this volume include: Modeling of strain relaxation and defect dynamics in buffer layers for semiconductor devices fabricated on lattice-mismatched substrates, which enables technology for advanced computer chips, multi-junction solar cells, detectors, and microwave transistors. Physical Unclonable Functions (PUFs) are probabilistic circuit primitives that extract randomness from the physical characteristics of devices. One of the papers outlines PUF design based on resistor and capacitor variations for low pass filters (LoPUF). Spatial wavefunction switching (SWS) FETs, which can process 2-bits per FET using CMOS-SWS logic, thus enabling multivalued logic (MVL) and compact DRAMs. Perimeter gated single-photon avalanche diode (PGSPAD). The applied voltage at the gate terminal modulates the electric field, making it uniform throughout the junction. This gating technique is an efficient method to prevent premature edge breakdown, one of the major problems in operating avalanche photodiodes implemented in CMOS process. In summary, papers selected in this volume cover various aspects of high performance logic and circuits for high-speed electronic systems. © 2019 by World Scientific Publishing Co. Pte. Ltd. All rights reserved.
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (International Journal of High Speed Electronics and Systems, 2019)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (High Performance Logic and Circuits for High-Speed Electronic Systems, 2019)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy